2021
DOI: 10.1186/s12957-021-02422-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of single-incision laparoscopic distal gastrectomy guided by ERAS and the influence on immune function

Abstract: Background To evaluate the immune function of gastric cancer patients after single-incision laparoscopic distal gastrectomy (SIDG) or multiport laparoscopic distal gastrectomy (MLDG) guided by enhanced recovery after surgery (ERAS). Methods A retrospective cohort study was performed on 120 patients who underwent laparoscopic distal gastrectomy for gastric cancer. The patients were divided into two groups according to operation method: group A (MLDG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…revealed that the serum immunoglobulin levels of piglets supplemented with C. butyricum and Enterococcus faecalis increased sharply in IgA, IgG and IgM levels ( 30 ). CD3 + T cell is the main reference index of immune function, and can be used as the total cellular immune state of the body ( 31 ). This study indicated that the index changes of CD3 + T cell, CD4 + T cell and CD4 + /CD8 + ratio in patients taking C. butyricum orally after gastrectomy were better than those without administration.…”
Section: Discussionmentioning
confidence: 99%
“…revealed that the serum immunoglobulin levels of piglets supplemented with C. butyricum and Enterococcus faecalis increased sharply in IgA, IgG and IgM levels ( 30 ). CD3 + T cell is the main reference index of immune function, and can be used as the total cellular immune state of the body ( 31 ). This study indicated that the index changes of CD3 + T cell, CD4 + T cell and CD4 + /CD8 + ratio in patients taking C. butyricum orally after gastrectomy were better than those without administration.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, related studies have demonstrated that the inflammatory response (tissue necrosis, activation of immune response, secretion of cytokines) plays an important role in the occurrence, development and metastasis of tumors [ 15 , 16 ]. In clinical practice, medical staff often use various methods such as enteral nutrition support and combined ERAS to adjust the immunity of cancer patients to improve the prognosis of patients [ 17 , 18 ]. In the early stage, the inflammatory response is induced and the anti-tumor immune response is inhibited, thereby promoting growth of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…With advancements in laparoscopic techniques and tools, single-incision laparoscopic surgery (SILS) has also been developed. Some studies have compared operative outcomes among various combinations of surgical methods and conventional or ERAS care [19,20]. Although no difference was observed in complications or readmission rates, the group that received ERAS care demonstrated a significantly shorter LOS than the other two groups receiving conventional perioperative care.…”
Section: ) Surgical Approachmentioning
confidence: 99%
“…In the multivariable analysis, perioperative ERAS care was a significant factor in reducing LOS, while SILS was not. Another study [20] compared SILS and multiport laparoscopic surgery while implementing ERAS perioperative care in gastric cancer cases. However, only the C-reactive protein level was significantly lower in the SILS group on the third postoperative day.…”
Section: ) Surgical Approachmentioning
confidence: 99%